Use of a card game tool to capture end users’ preferences and add sustainability value to social housing projects - Carvalho, Adrieli Cristina Vieira Vieira de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
The construction industry is increasingly adopting sustainable strategies to achieve efficiency targets and reduce environmental impacts. Despite this increase, some barriers are still perceived in the real estate market for sustainable buildings. One of them is the delivery of products that are not aligned with the needs and values of end users. This paper investigates the aspired sustainability values in housing projects based on the concept of stated preferences. A card game tool was developed based on the AQUA - HQE™ rating system and applied to ask a 164-respondent sample, assembled from four social housing projects to identify their preferences regarding sustainable construction. Responses were statistically analyzed based on bootstrap confidence values and on the index of general significance (IGS) of each sustainable value attribute. Results show a sustainable value hierarchy, in which the health and safety parameters were the most valued. This study confirms the validity of using a set of illustrated cards as a potential tool for identifying sustainability values end users bear and consequently improving decision-making process within sustainable products development.